K вonpocy об этнической пpинадлежности и аpxeологической кyльтype Киммерийцев, II. "Paннескифские находки в Малой Азии" - Иванчик, A.И.
Ivan?ik, A.I., On the Question of Ethnic Origin and Archaeological Culture of the Cimmerians, II. Early Scythian Finds in Asia Minor